Analyzing Deixis of English Speech by Kim Namjoon (BTS) at the United Nations - St. Ika Susanti; Iin Widya Lestari; Khoirul Wafa (PT. Global Research Collaboration, 2023)
Humans, as social beings, naturally interact to fulfill various life needs. This study aimed to analyze different deixis types in Kim Namjoon's speech and understand their meanings. The research employed Stephen C. Levinson's Theory and utilized a descriptive qualitative method with a content analysis approach. The findings revealed five deixis categories in Kim Namjoon's speech: personal, spatial, temporal, discourse, and social. These were distributed as follows: 129 (65.8%) personal deixis, 15 (7.7%) spatial deixis, 10 (5.1%) temporal deixis, 31 (15.8%) discourse deixis, and 11 (5.6%) social deixis. In total, 196 deixis instances were identified in Kim Namjoon's speech. His speech, titled